Change model for a school-based program to promote oral hygiene practices among Indian school children - Mehra, Rashmi (International Journal Of Community Medicine And Public Health, 2021)
The present paper addresses basic evaluation and procedural concepts that are involved in the process of implementing a school-based program to promote oral hygiene practices among Indian school children using the I-change intervention mapping model. Core components for effective intervention design and implementation are presented as part of a comprehensive model composed of six stages along with in depth discussion about sustaining each step under the I-change model providing with the imminent need for such a school based program in India. This model systematically addresses the design program, the production of said program called insta-brush. Special attention has been given to the planned program implementation delineating suggested sequence of implementation followed by comprehensive measurement of the impact of the program with proposed process and summative evaluation plans. Assessment tools and evaluation strategies are recommended and illustrated based on evaluations of interventions implemented in school based oral health programs worldwide.